P2-S2.20 The association study of job mobility and HIV/STI prevention in female sex workers of Hunan province, China. (10th July 2011) - Zheng, Z; Jiang, N
Abstract : Background: The job mobility of female sex workers (FSWs) is the working experience that keep low level status and no rising opportunity among all previous jobs before FSWs enter of commercial sex work. To understand the characteristics of job mobility and accessibility to health information and service before engaging in sex work, the study was implemented to its impact on HIV/STD prevention. Strategies and mechanism were explored to provide HIV/STD information and health service to FSWs before they engaging in sex work. Methods: This study was conducted at two cities of Hunan province in September to October, 2009. Ethical approval was obtained from the institutional review board of institute of Dermatology, Chinese Academy of Medical Sciences (CAMS). This study adopted stratified sampling with proportional allocation. Mapping was fulfilled respectively according to distribution of Entertainment Establishment in two cities. FSWs populations were classified into high tier, medium tier and low tier according to the type of working places and the price of sex services. Participants were determined after setting up sampling framework. Data were collected through questionnaire survey and in-depth interview and questionnaire survey on the basis of informed consent written by participants. The data were double entered, using Epidata software, by two researchers independently and were checked to assure accuracy and completeness. Statistical analysis of data was performed with SAS version 9.1 (SAS Institute Inc, Cary, NC). Univariate and multivariate analysis were used to examine for associations between variables of interest. Results: 207 FSWs were recruited in Zhangjiajie city and Shimen county of Hunan province. Of all respondents, the median age was 22 (range 16–48), 72.5% were unmarried, 67.8% had junior high school education, and 75.6% were from rural areas. 65.3% of the respondents once migrated to one or more places outside original hometown for job-seeking. 15.2% of 207 respondents reported sex work as their first job, while the rest reported at least one job before engaging in sex work. No significant differences were found among monthly salary of all previous jobs before sexual services. Significant differences were found between average monthly salary of previous jobs and sexual services at two sites. The median monthly income of sex work was about four times as much as that of their all previous jobs. 83.7% of the respondents were engaged in individual business or private enterprise before sexual services, especial for working in service industry or factory. In the opinion of job-seeking way and approach, 14.7% of the respondents had obtained employment information from regular channel or official agent of labour management department etc. Only 28.1% of the respondents had gained HIV/STD prevention information before sexual services. 89.7% of the respondents were not provided any counselling or reproductive health services in the course of job mobility, however 67.5% of the respondents would be eager for receiving periodic and accessibility of reproductive health services. Conclusions: Job mobility of FSWs before sex work is objective phenomenon at research areas. Occupational status and income is low level and poor work conditions of all previous jobs before sex work. It existed impossible rising opportunity between different jobs and positions. That is the horizontal characteristics of job mobility for FSWs population. It is significant association between low occupational status and lack of health relevant information and service, while poor accessibility to health information and services is associated with low occupational status in the course of jobs-seeking and job mobility. Adverse impact were exerted to accessibility of health information and services for FSWs after entering of commercial sex work. The advice of the study is obvious and necessary that except for employment guidance, the students of junior high school should be educated with reproductive health and HIV/STD before graduation in research areas or other rural areas.